Calculating the price response of stocks in emerging markets - Nonyane, E T (My University, 2019)
In stock markets, price response refers the change in the market price subsequent to a trade. It can result in unintended costs and lead to a substantial amount of risk. To quantify the e ect of price response, several measures of it|such as price impact and bare response|have introduced and analysed in the literature. This dissertation uses tick data from the Thompson Reuters Tick History database and some of the previously introduced price response measure to examine the price response of trades for a selection of emerging market stocks. Although price response is widely discussed and measured for the European and North American stock markets, few studies of it exit for emerging markets. Thus, we attempt to ll the gap in the literature by considering stocks from Brazil, Russia, India, China, South Africa and Kenya and Egypt. We suggest and document a highly scalable and reproducible work- ow for calculating price response for these markets. In accord with the ndings in developed markets, we nd that the price response of trades tends to increase with traded volume and decrease over time. We also nd that the most actively traded stocks (those with a high average daily volume or average daily traded value) tend to exhibit a lower degree of price response
Programme in Computational and Applied Mathematics, School of Computer Science and Applied Mathematics